Prenatal valproic acid-induced autism marmoset model exhibits higher salivary cortisol levels - Nakamura, Madoka; Nakagami, Akiko; Nakagaki, Keiko; Yasue, Miyuki; Kawai, Nobuyuki; Ichinohe, Noritaka (Frontiers in Behavioral Neuroscience, 2022)
Individuals with autism spectrum disorder (ASD) are exposed to a variety of stressors owing to their behavioral traits. Cortisol is a hormone typically associated with stress, and its concentration and response to stress are higher in individuals with ASD than in controls. The mechanisms underlying cortisol dysregulation in ASD have been explored in rodents. Although rodent models have successfully replicated the major symptoms of autism (i.e., impaired vocal communication, social interaction deficits, and restricted/repetitive patterns of behavior), evidence suggests that the hypothalamic-pituitary-adrenal (HPA) axis system differs between rodents and primates. We developed an ASD model in the common marmoset (Callithrix jacchus), a New World monkey, utilizing prenatal exposure to valproic acid (VPA). In this study, we collected the salivary cortisol levels in VPA-exposed and unexposed marmosets in the morning and afternoon. Our results revealed that both VPA-exposed and unexposed marmosets showed similar diurnal changes in cortisol levels, which were lower in the afternoon than in the morning. However, heightened cortisol levels were observed in VPA-exposed marmosets in the morning, but not in the afternoon. These results are consistent with those of ASD in humans. Our results suggest that VPA-exposed marmosets show similarities not only in their behavioral patterns and brain pathologies, which we have reported previously but also in hormonal regulation, validating the usefulness of VPA-exposed marmosets also as a tool for ASD stress research.